PENGARUH KUALITAS PELAYANAN DAN KEMAMPUAN MANAJERIAL PENGURUS TERHADAP KEPUASAAN ANGGOTA KOPERASI KARYA BUNDA DI KOTA PAYAKUMBUH - Mutia Rahmah; Suarman Suarman; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to know the influence of the quality of service and managerial capabilities of members of the Executive Board against our satisfaction cooperative work of Karya Bunda of payakumbuh. The population in this research is the entire members of the Cooperative work of Karya Bunda in the town of Payakumbuh totalling 153 people and sample numbering 111 people with random technique. The data used are the primary data through dissemination of the question form and documentation. Research using quantitative methods and anilisis multiple linear regression test data. Based on the research results influence quality of managerial capabilities and caretaker of the Ministry against our satisfaction cooperative members Karya Bunda in payakumbuh contributed to the influence of 38.6%, while the rest of 61.4% are affected by other variables that were not examined in this study. In this study recommend to the Executive Board of the cooperative work of Karya Bunda in the town of Payakumbuh in order to maintain the quality of service provided to members of the Cooperative work of Karya Bunda in the town of Payakumbuh so satisfaction permanent members as well as the administrators of the cooperative work of Karya Bunda in the town of Payakumbuh enhanced capabilities in order to be manajerialnya so that the resolution of the problems relating to members can be resolved properly.Key Words: Cooperative, Members, Services, Managerial, Satisfaction.